Is University Students’ Value Orientation toward Integrity Behind Their Decision to Cheat or Not Cheat in Exams? - Anggara Wisesa; Dematria Pringgabayu; Adita Pritasari; Nurfaisa Hidayanti; Dany Muhammad Athory Ramdlany (Gadjah Mada International Journal of Business, 2019)
Organizational values characterize every activity, including the behavior of the members of an organization, and their decision-making. However, there are moments in which the members of the organization violate the values, even though they know they should not. It also happens to university students. This fact brings us to reflect on how the values are interpreted in value orientation. By employing the phenomenological method using Kohlberg’s constructivist theory of moral development stages, this study explored the value orientation towards integrity in business school students’ decisions to cheat or not. The result indicates that even for students who face the same decision to cheat or not, their decision is affected by how they understand the value of integrity, which depends on their value orientation and their cognitive moral development. Most respondents had a mindset of egoistic value orientation, which is more concerned with the benefits and payback when making a decision. Most cases happened without there being a prior decision to cheat; the decision is made at the time of the exam by considering the emerging internal or external situational factors.